2004
DOI: 10.1021/ja0486059
|View full text |Cite
|
Sign up to set email alerts
|

Nanotube Molecular Transporters:  Internalization of Carbon Nanotube−Protein Conjugates into Mammalian Cells

Abstract: The interactions between various functionalized carbon nanotubes and several types of human cancer cells are explored. We have prepared modified nanotubes and have shown that these can be derivatized in a way that enables attachment of small molecules and of proteins, the latter through a novel noncovalent association. The functionalized carbon nanotubes enter nonadherent human cancer cells as well as adherent cell lines (CHO and 3T3) and by themselves are not toxic. While the fluoresceinated protein streptavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
373
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,238 publications
(387 citation statements)
references
References 21 publications
11
373
1
2
Order By: Relevance
“…26,32 Some experimental observations had shown that very small nanoparticles and nanotubes, with size below the supposed lower critical radius, were found inside cells. [58][59][60] This observation seemed to contrast with both other experimental observations, as well as with predictions from theory and simulations.…”
Section: Predicting and Controlling Nanoparticles Endocytosiscontrasting
confidence: 74%
“…26,32 Some experimental observations had shown that very small nanoparticles and nanotubes, with size below the supposed lower critical radius, were found inside cells. [58][59][60] This observation seemed to contrast with both other experimental observations, as well as with predictions from theory and simulations.…”
Section: Predicting and Controlling Nanoparticles Endocytosiscontrasting
confidence: 74%
“…Carbon nanotubes have greatly advanced these fields. Similarly as other nanoparticles, carbon nanotubes can be readily taken up by cells and are noncytotoxic within a certain concentration limit if suitably functionalized [25] [26]. The main finding of this study was that HTT2800 has a significant effect on intracellular lipid accumulation in C2C12 cells.…”
Section: Discussionmentioning
confidence: 69%
“…suggested that an energy-dependent endocytosis mechanism is responsible for the uptake of carbon nanotubes [17]. Endocytosis is the process by which cells absorb molecules or substances from outside the cell by engulfing them with the cell membrane.…”
Section: Discussionmentioning
confidence: 99%